2012
DOI: 10.1038/modpathol.2011.190
|View full text |Cite
|
Sign up to set email alerts
|

Secretory breast carcinoma: a clinicopathological and immunophenotypic study of 15 cases with a review of the literature

Abstract: Secretory breast carcinoma is a rare breast cancer with indolent clinical behavior. Recent research showed that secretory breast carcinoma belongs to the phenotypic spectrum of basal-like breast carcinomas. In this study, a clinicopathological and immunophenotypic analysis of secretory breast carcinomas from 15 Chinese patients was conducted. This patient group consisted of 2 males and 13 females, with ages ranging from 10 to 67 years old (median, 36 years old). All patients presented with a painless and firm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
87
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 40 publications
5
87
1
Order By: Relevance
“…Lamovec and Bracko reported 4 cases of SBC in their retrospective series of 7038 breast carcinoma cases [4], and Botta et al [5] found one case of SBC among 3000 breast carcinoma cases. Li et al reported 15 cases in their pathologic review of 10000 breast carcinoma cases [6]. …”
Section: Discussionmentioning
confidence: 99%
“…Lamovec and Bracko reported 4 cases of SBC in their retrospective series of 7038 breast carcinoma cases [4], and Botta et al [5] found one case of SBC among 3000 breast carcinoma cases. Li et al reported 15 cases in their pathologic review of 10000 breast carcinoma cases [6]. …”
Section: Discussionmentioning
confidence: 99%
“…Morphologically it is a compact tumor with solid, papillary, tubular, and microcystic areas. Though most secretory breast carcinomas express basal-like markers, it is thought that aggressive treatment should be avoided in view of their indolent nature [10].…”
Section: Discussionmentioning
confidence: 99%
“…However in older patients chance of recurrence is increased. [3,14] Our case was a 60 year old female with T 2 N 1 M x , BR grade 2 tumor. The secretory material in the lumina were PAS positive.…”
Section: Discussionmentioning
confidence: 99%